IMPLEMENTASI INSTRUMEN PENILAIAN PERKEMBANGAN KOGNITIF ANAK USIA 5-6 TAHUN DI TK SANTO THOMAS 2 MEDAN - Anita Yus; Artha Mahindra Diputera; Bella Agustiara; Ester Sianipar; Roida Ayu Boangmanalu; Bintang A.G Naibaho; Hanisa Yesilistiawati Br Tobing; Citra Alwiyah Purba (ADIBA : JOURNAL OF EDUCATION, 2023)
This article or article aims to assess aspects of cognitive development by implementing an assessment instrument that the researcher deliberately made for students at Kindergarten Santo Thomas 2 as an effort to find out how far a child's cognitive development has progressed. This research is focused on looking at children's cognitive development in order to provide feedback on the results. The data collected through observation and analyzed qualitatively. The research sample was at TK B Santo Thomas in class B Ceria and the research subjects consisted of 13 students. This study concluded that it is important to measure the development of children's cognitive aspects in order to determine steps in providing feedback on children's learning outcomes.